Possible applications of information theory in logistics - (:unkn) unknown (My University, 2011)
Some ideas are presented how methods from information theory might be applied to logistics, more exactly to RFID security problems. Identification codes might be useful in a nosiy environment. Network coding could help in encryption and authentification. © 2011 IEEE.
Keywords: identification codes; location of attackers; network codes; RFID security